2018
DOI: 10.1590/1413-81232018233.00102016
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimento e percepção sobre o HPV na população com mais de 18 anos da cidade de Ipatinga, MG, Brasil

Abstract: Conhecimento e percepção sobre o HPV na população com mais de 18 anos da cidade de Ipatinga, MG, BrasilKnowledge and perception of HPV in the population over 18 years of age in the city of Ipatinga -State of Minas Gerais, Brazil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0
57

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 17 publications
3
6
0
57
Order By: Relevance
“…These results corroborate Abreu et al, who showed that participants who reported high knowledge about HPV had a higher level of schooling and average family income (p < 0.001) [35]. Individuals with higher socioeconomic status possibly have more access to information, and consequently could be more aware regarding HPV infection and prevention measures [21,23,34,35]. The main source of information cited by participants in our study was television/radio.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results corroborate Abreu et al, who showed that participants who reported high knowledge about HPV had a higher level of schooling and average family income (p < 0.001) [35]. Individuals with higher socioeconomic status possibly have more access to information, and consequently could be more aware regarding HPV infection and prevention measures [21,23,34,35]. The main source of information cited by participants in our study was television/radio.…”
Section: Discussionsupporting
confidence: 91%
“…The main source of information cited by participants in our study was television/radio. However, such media is not considered the most appropriate or it is not enough to improve knowledge and lead to prevention behavior [35,36]. Moreover, low level of schooling can make it difficult to understand the content transmitted by these or other sources of information [21,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Estudos revelam que o Papiloma Vírus Humano (HPV), é o principal agente oncogênico do câncer de colo uterino, sendo que o contágio usualmente ocorre no início da vida sexual, principalmente na adolescência, e decorre também do maior número de parceiros sexuais 13 . A incidência do HPV em adolescentes foi ilustrada em pesquisas, revelando taxas de até 48,9% em grupos amostrais, das quais cerca de 28,5% apresentaram infecções múltiplas, sendo o HPV-16 o subtipo mais comum 14 .…”
Section: Discussionunclassified
“…4 Além disso, a taxa infecção desse vírus varia de acordo com a faixa etária, sendo maior nas adultas jovens sexualmente ativas e progressivamente menor, nos intervalos etários mais velhos. [6][7] Além do HPV, os estudos apontam diversos outros fatores de risco associados ao câncer de colo do útero, tais como o início precoce da atividade sexual, multiplicidade de parceiros, uso prolongado de contraceptivos orais, múltiplas gestações, doenças sexualmente transmissíveis, tabagismo, baixo consumo de alguns nutrientes, pobreza, entre outros. 8-9-10 No Brasil, a prevenção contra o câncer cervical é classificada em primária e secundária.…”
Section: Introductionunclassified